All the Turns in ’Aestheticizing’ Life - Margolis, Joseph (Filozofski vestnik, 2016)
What we face today is the recovery of critical judgment under the condition of changing history. Aestheticizing bids us to abandon the need for legitimation by way of refocusing the public impulses of the “people” (whether in Heidegger’s way or Rorty’s) or assures us without argument that the aestheticizing impulse is reliably generous in the best democratic sense (as with Shusterman and Welsch). The author finds himself unwilling to trust either tendency and believes, rather, that if there is a disciplined debate that may be mounted, we will find that we have reclaimed the question of moral or ethical direction which would mean outflanking both the revelatory and the postmodernist options once again – without falling back to modernist assurances.